Rising threat of H1N1 Cases in Dakshina Kannada, India: An Epidemiological Assessment from January 2011 To August 2017 - Rao, Ramakrishna; Vittaldas, Rajesh Bekal; Dsouza, Jyoshma Preema (Indian Journal of Community Health, 2019)
Background: H1N1 or swine flu is a disease caused my influenza virus of family Orthomyxoviridae. Initial cases in India were seen in 2009 and ever since then it has been adding to the mortality rate over the years across various parts of the country. Dakshina Kannada district of Karnataka, India, had several cases of H1N1. But despite the efforts, the magnitude is rising inconspicuously. Aim & Objective: Assessment of H1N1 cases throughout Dakshina Kannada district from Jan 2011 to August 2017. Objectives: To observe the disease trend, its factors and provide certain recommendations to control the disease and promote Health. Material & Methods:H1N1 cases notified to District surveillance unit from all the Health collaborated settings over a period of six years from January 2011 to August 2017 were assessed to measure the burden of the disease across different age groups and Gender. Result: The study revealed a considerable increase in H1N1 cases compared to previous years with peak during monsoon and difference in risk among the gender. Conclusion: Vaccination of Health professionals, High alert for travelers, Pregnant women and individuals with co-morbid conditions is essential. Control of disease transmission with early diagnosis, isolation and treatment, effective vaccination to high risk individuals will be helpful to reduce disease burden